A series of Ni–Al2O3 catalysts derived from layered double hydroxides for vapor phase catalytic exchange between water and hydrogen. (13th September 2021) - Li, Peilong; Hu, Xiaoyu; Zhang, Zexuan; Wen, Ming; Chen, Min; Yu, Bin; Zhou, Linsen; Yong, Wenwen; Song, Jiangfeng; Zhang, Xin; Luo, Wenhua
Abstract: Fabricating supported metal catalysts from layered double hydroxides (LDHs) is a promising strategy to develop high-efficient and low-cost materials for water detritiation. In this work, a series of NiAl-LDHs with different Ni/Al ratios were prepared and reduced to obtain Ni-based catalysts with Al2 O3 support (Nix -Al2 O3 ) and further tested in vapor phase catalytic exchange (VPCE) process. Results revealed that the activity of catalysts varies with Ni/Al molar ratios and is also affected by textural properties. Remarkably, the Ni2 –Al2 O3 with the Ni/Al molar ratio of 2 exhibited excellent activity, due to the balanced factors of Ni content, specific surface area, Ni particle size and Al 3+ configuration proportion. This study sheds some light on reaction mechanism of VPCE process and may be applicable for the rational design of highly efficient catalysts. Graphical abstract: Image 1 Highlights: A series of LDHs-derived Nix -Al2 O3 catalysts were prepared for VPCE process. Ni2 –Al2 O3 derived from Ni2 Al-LDHs has prominent catalytic activity. Ni0.5 -Al2 O3 derived from Ni0.5 Al-LDHs shows excellent Ni atom utilization. Ni content, particle size and Al 3+ property exhibit synergetic effects on VPCE.